2018
DOI: 10.1155/2018/1614683
|View full text |Cite
|
Sign up to set email alerts
|

Association of PD-1 and PD-L1 Genetic Polymorphyisms with Type 1 Diabetes Susceptibility

Abstract: Aims The programmed death- (PD-) 1/PD-1 ligand (PD-L) pathway plays an important role in regulating T cell activation and maintaining peripheral tolerance. Accumulated studies showed that PD-1/PD-L1 pathway was involved in the development of type 1 diabetes (T1DM). Since the genetic background of type 1 diabetes differs greatly among the different population, we aim to investigate the association of genetic polymorphisms in PD-1 and PD-L1 with T1DM susceptibility in Chinese population. Methods In total, 166 T1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 29 publications
(35 reference statements)
1
31
0
Order By: Relevance
“…Instead, the allele of HLA A ∗ 0201 in this patient was reported to be relevant with diabetes susceptibility ( 4 ), which has not been reported in the onset diabetes by anti-PD-1 treatment. In addition, studies about genetic polymorphisms within PDCD1 (encoding PD-1) identified single nucleotide polymorphisms (SNPs) of rs111568821, rs2227981, rs2227982, and rs4143815 as significantly associated with type 1 diabetes susceptibility ( 15 , 16 ). Combined ICB treatment might also carry an increased risk of diabetes compared with that of monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the allele of HLA A ∗ 0201 in this patient was reported to be relevant with diabetes susceptibility ( 4 ), which has not been reported in the onset diabetes by anti-PD-1 treatment. In addition, studies about genetic polymorphisms within PDCD1 (encoding PD-1) identified single nucleotide polymorphisms (SNPs) of rs111568821, rs2227981, rs2227982, and rs4143815 as significantly associated with type 1 diabetes susceptibility ( 15 , 16 ). Combined ICB treatment might also carry an increased risk of diabetes compared with that of monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent studies have reported that a single-nucleotide polymorphism (SNP) in PDCD1 is associated with the development of autoimmune diseases (SLE, type 1 diabetes, progressive MS, Vogt-Koyanagi-Harada disease, Graves' disease, and RA), suggesting that PDCD1 may be involved in the maintenance of tolerance (20, 108). For instance, the SNP rs4143815 in PD-L1 is associated with T1DM and could be a new biomarker for predicting T1DM susceptibility (109, 110).…”
Section: Autoimmunitymentioning
confidence: 99%
“…Within the context of T1D, the PD-1/PD-L1 axis is pivotal to autoimmunity, as seen by abnormalities in PD-L1 presentation in human patients with T1D ( 14 ) and disease halting in transgenic models expressing PD-L1 ( 15 ). Strategies aimed at using PD-L1 to control disease progression and diabetes reversal have ranged from genetically modifying islets to express PD-L1 ( 16 ) to improve graft survival in allogeneic transplantation models ( 17 ) to the delivery of antigen-presenting cells genetically or chemically modified to overexpress PD-L1 ( 18 ).…”
Section: Introductionmentioning
confidence: 99%